2023
DOI: 10.1080/10717544.2023.2168793
|View full text |Cite
|
Sign up to set email alerts
|

Silk nanoparticles for the protection and delivery of guava leaf ( Psidium guajava L.) extract for cosmetic industry, a new approach for an old herb

Abstract: Guava ( Psidium guajava L.) is a well-known plant containing high levels of natural antioxidants, the phenolic compounds, which have been employed in numerous cosmetic products. However, these molecules are unstable to oxidants, light, temperature, pH, water, and enzymatic activities. Therefore, to enhance their stability and preserve their antioxidant activity, this study investigated the silk fibroin nanoparticles (SFNs) ability to encapsulate, deliver, and heat-protect the phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Recently, Pham et al observed that scavenging activities of an encapsulated active gradually increased over time, suggesting that the antioxidant effectiveness may be directly related to the release of the active from the NPs. 107 Based on our drug release studies shown above, it is expected that FA would also exhibit a gradual interaction with DPPH due to its sustained release from the polymeric NPs. However, we were unable to confirm this behaviour after incubating FA-loaded PLGA NPs in the presence of an ethanolic DPPH solution (50% v/v) at shorter incubation times (5, 10, and 15 min).…”
Section: Resultsmentioning
confidence: 92%
“…Recently, Pham et al observed that scavenging activities of an encapsulated active gradually increased over time, suggesting that the antioxidant effectiveness may be directly related to the release of the active from the NPs. 107 Based on our drug release studies shown above, it is expected that FA would also exhibit a gradual interaction with DPPH due to its sustained release from the polymeric NPs. However, we were unable to confirm this behaviour after incubating FA-loaded PLGA NPs in the presence of an ethanolic DPPH solution (50% v/v) at shorter incubation times (5, 10, and 15 min).…”
Section: Resultsmentioning
confidence: 92%
“…The process of extracting and refining regenerated fibroin from silk cocoons was conducted with reference to a prior publication [ 39 ]. In brief, the silk cocoons (10 g) underwent sericin-removal process with 200 mL Na 2 CO 3 (0.5% w/v) at 100°C for 1 h, washed thrice with water, and air-dried.…”
Section: Methodsmentioning
confidence: 99%
“…The findings demonstrated that the guava extract nearly completely lost all of its antioxidant capacity after being exposed to a high temperature of 70°C for 24 hours, but the extract-loaded SFNs were able to retain the extract activity. The efficacy and safety of cosmetics have improved as a result of all these nanoformulations [81].…”
Section: Innovations In Cosmetic Ingredientsmentioning
confidence: 99%